(untitled) (Web of Teachers: Inderscience Research, 2025)
Pedagogical monitoring of football players is considered as an important process in the history of sports. This process is carried out in order to develop the players themselves, increase their success in sports and improve the overall results of the team. Pedagogical monitoring includes observing, evaluating and analyzing the process of training and education of players. The main goal of this process is to determine the individual characteristics, abilities and level of development of players.